Metabolic Responses in Leaves of 15 Italian Olive Cultivars in Correspondence to Variable Climatic Elements - Ilaria Colzi; Elettra Marone; Simone Luti; Luigia Pazzagli; Stefano Mancuso; Cosimo Taiti (Plants, 2023)
This study aims to evaluate the metabolic changes that occurred in olive leaves as responses over time to variations in climatic elements. Rainfall, temperature, and solar radiation data were collected over 4 months (August–November) to assess the impact of different climatic trends on the metabolism of the leaves of 15 Italian olive cultivars, cultivated at the experimental farm of the University of Florence. The net photosynthetic rate (AN) and stomatal conductance (gs), measured as main indicators of primary metabolism, were mainly influenced by the “cultivar” effect compared to the “climate” effect. The lowest AN value was showed by “Bianchera”, while “Ascolana” recorded the highest (8.6 and 13.6 µmol CO2 m−2s−1, respectively). On the other hand, the secondary metabolism indicators, volatile organic compound (VOC) and oleuropein (OL) content, were much more influenced by climate trends, especially rainfall. A phase of high rainfall caused a significant increase in the VOCs emission from leaves, even with different behaviors among the genotypes. The highest differences were observed between “Maiatica di Ferrandina”, with the highest average values (~85,000 npcs), and “Frantoio”, which showed the lowest (~22,700 npcs). The OL content underwent considerable fluctuations in relation to the rainfall but also appeared to be controlled by the genotype. “Coratina” always showed the highest OL concentration (reaching the maximum ~98 mg g−1), indicating the great potential of this cultivar for the industrial recovery of OL.